Teoría de Juegos e Individualismo Metodológico de Jon Elster - Pedroza, René (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2000)
Education as object of inquiry is susceptible to multiple interpretations, which -most of them- run the risk of falling only in the understanding of structural factors or in internalist aspects. Reason why one feels like exploring routes that do not engage in a determinist paradox of the type: society determines education or education determines society. That is the reason for this document to pursue a double purpose: one show the contributions of Jon Elster to the study of the social aspect; and the other, the ludic pretension of attracting Elster for the analysis of education. The methodological individualism and the theory of the games both part from the importance of recognizing the individuals as capable of taking decisions once they have valued the intentionalities that may arise in the own representation of the stage to which the decision corresponds. Let’s say that there is a comprehension of the different actors before they carry out an action, which is valued in terms of the maximization of results in close relation to the interests of the ones involved. The article is divided in two great sections: the first one, a panoramic view of Jon Elster is presented, divided in a brief portrait, the context of his theoretical assumptions, the itinerary of his through his main works and his contribution about the explanation of the social. In the second one, the analysis of education is explored from the vision of the methodological individualism, for that purpose, an initial comment is offered about the meaning of such a intention, to proceed later on with the representation of different examples of maximazing the notions of Elster in the classroom and the academy.